Open Loop and Closed Loop Power Control Analysis on LTE - Norma Amalia; Eka Setia Nugraha; Muntaqo Alfin Amanaf (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
LTE downlink is using Orthogonal Frequency Division Multiple Access (OFDMA) multiple access system which have high invulnerability from multipath problem. One of the weakness of OFDM system is the high level from Peak to Average Power Ratio (PAPR) that requires higher level transmit power for maintaining the Bit Error Rate (BER) requirement. Using uplink scheme with Single Carrier FDMA (SC-FDMA) which is OFDMA modification, will be offered better level of PAPR than its conventional OFDM. The main problem of using OFDMA is the high level of PAPR, while using SC-FDMA the problem is intra-cell interference. Intra-cell or inter-cell interference is the common problem that can reduce the LTE performance. Minimizing received power for each users (UE) which is still at acceptable tolerance parameter, can be used for reducing the interference problem to another UE. Power control is the appropriate solution for minimizing the interference level. In this paper will be analyzed the power control using open loop and closed loop scheme at LTE network. The simulation result shows that without power control schemes, the transmit power of UE was 23 dBm. While, after applying power control scheme, the transmit power was 18.8 dBm at α=0.4 of open loop condition and 9.05 dBm at closed loop condition. Using this transmit power value as the UE power can improve the SINR performance. The SINR average value without power control scheme was only 20.38 dB which is lower than using open loop scheme was achieved 22.44 dB, and 24.02 dB at closed loop scheme.